Shoreline change analysis and its impact on coastal communities using remote sensing and GIS in the Kedungsepur Metropolitan area - Fariz, Trida Ridho; Martuti, Nana Kariada Tri; Haris, Amnan; Suhardono, Sapta; Damayanti, Meilinda; Eralita, Norma (Center for Science and Technology, IAIN Surakarta, 2025)
Shoreline mapping plays an important role in sustainable coastal management, particularly in strategic areas such as the Kedungsepur Metropolitan Area. This study aims to analyzes shoreline changes and identifies their impact on coastal communities. Shoreline extraction was conducted using remote sensing data from Landsat satellite imagery, while the analysis of shoreline changes was performed using the Digital Shoreline Analysis System (DSAS) within a Geographic Information System (GIS) environment. The results reveal that shoreline changes – both erosion and accretion – occurred across Kendal Regency, Semarang City, and Demak Regency. The most severe coastal erosion was identified in Bedono Village (Demak Regency), while the highest accretion occurred in Pidodo Kulon Village (Kendal Regency). When analyzed by watershed units, the highest accretion was found in the Bodri Watershed, one of the priority areas for revitalization. These findings highlight the need for integrated policy approaches that connect coastal and watershed management to ensure long-term sustainability.